2012
DOI: 10.1371/journal.pone.0038694
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Active Canonical NF-κB Pathway Induces Severe Bone Loss in Mice

Abstract: Physiologic osteoclastogenesis entails activation of multiple signal transduction pathways distal to the cell membrane receptor RANK. However, atypical osteoclastogenesis driven by pro-inflammatory stimuli has been described. We have reported recently a novel mechanism whereby endogenous mutational activation of the classical NF-κB pathway is sufficient to induce RANKL/RANK-independent osteoclastogenesis. Here we investigate the physiologic relevance of this phenomenon in vivo. Using a knock-in approach, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…30 Previous reports suggested that TNF-a enhances osteoclastogenesis and inhibits osteogenesis at an early stage of inflammation, but induces osteogenesis at the later tissue repair stages of inflammation. 30 The role of NF-kB in osteogenesis in previous reports [31][32][33][34][35] and our current findings may be due to different time points of evaluation, different proinflammatory stimuli, and the specific osteogenic markers tested.…”
Section: Figmentioning
confidence: 69%
“…30 Previous reports suggested that TNF-a enhances osteoclastogenesis and inhibits osteogenesis at an early stage of inflammation, but induces osteogenesis at the later tissue repair stages of inflammation. 30 The role of NF-kB in osteogenesis in previous reports [31][32][33][34][35] and our current findings may be due to different time points of evaluation, different proinflammatory stimuli, and the specific osteogenic markers tested.…”
Section: Figmentioning
confidence: 69%
“…The Role of Cytokines in Inflammatory Bone Loss expression of constitutively active IKKb in Cd11b þ myeloid cells generates mice which exhibited decreased bone mass in trabecular bone due to increased number of osteoclasts on the trabecular bone surfaces (Otero et al, 2012a). For reasons not understood, no such changes were seen in cortical bone.…”
Section: Rankmentioning
confidence: 99%
“…The physiological relevance of this finding was demonstrated in vivo using a myeloid knock-in of the transgene IKK2SSEE. Phenotypic assessment revealed that expression of IKK2SSEE in the myeloid compartment induced significant bone loss in vivo [38], manifested by significant increase in the number and size of osteoclasts in trabecular regions, elevated levels of circulating TRACP-5b, and reduced bone volume. Mechanistically, IKK2SSEE induced high expression of not only p65/RelA but also p52 and RelB; the latter two molecules are considered exclusive members of the alternative NF-κB pathway.…”
Section: Role Of Individual Nf-κb Subunits and Kinases In Osteoclastsmentioning
confidence: 99%